A Systematic Literature Review on Teacher Performance: Determinants, Measurement, and Practical Implications in the Education Sector - Yolanda, Erika; Meiske Claudia; Rini Rahmawati (Cita konsultindo, 2025)
This study aims to map and analyze scientific literature related to the concept of teacher performance using the Systematic Literature Review (SLR) method. A total of 25 peer-reviewed articles published between 2020 and 2024 were analyzed to identify key themes, theoretical foundations, and practical implications. The results indicate that teacher performance is influenced by a combination of internal factors (such as self-efficacy, stress, and job satisfaction) and external factors (such as principal leadership, organizational climate, and digital transformation). The five key themes identified include: (1) self-efficacy and psychological factors, (2) school leadership and management, (3) job satisfaction and organizational climate, (4) work stress and burnout, and (5) digitalization and adaptation to technology. This synthesis also presents a conceptual model and theoretical-practical implications, which can serve as a basis for developing integrated teacher performance evaluation strategies in the post-pandemic era.